Rules and Beliefs of Relationship Permanence: Design and Validation of a Measure - Alejandra Elizabeth Pérez Pérez; Rozzana Sánchez Aragón (Interacciones)
Based on the perspective of Diaz-Guerrero (2003) concerning beliefs, norms, and values that control feelings, thoughts, and behaviors involved in the development, maintenance and dissolution of couple relationships, the study was conducted to assess the historical socio-cultural premises regarding to relational permanence in such relationships. To address this goal pair of studies was designed: 1) an exploratory study where 200 participants from Mexico City answered an open ended question. Based on the answers to the first study, an objective instrument with a Likert format was designed and administered to a sample of 334 adults. Following the procedure proposed by Reyes Lagunes & García y Barragán (2008), the scale consists of 32 grouped into five factors: Ideal relationship, Tradition thoughts, Loyalty, Satisfactory interaction and Coincide, these factors explained 69.88% of the total variance and have a .81 Cronbach’s Alpha Coefficient. The findings coincide with the foundations of the different theoretical perspectives of the study of relational permanence and included cultural aspects particular to the context of Mexican socio-culture, the findings and implications for future research are discussed in this way.